2020
DOI: 10.3390/cancers12082090
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Quantification of Non-Coding RNA Originating from the rDNA in Human Glioma Cells

Abstract: Ribosomal DNA is one of the most conserved parts of the genome, especially in its rRNA coding regions, but some puzzling pieces of its noncoding repetitive sequences harbor secrets of cell growth and development machinery. Disruptions in the neat mechanisms of rDNA orchestrating the cell functioning result in malignant conversion. In cancer cells, the organization of rRNA coding genes and their transcription somehow differ from that of normal cells, but little is known about the particular mechanism for this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…It is demonstrated that the pre-promoter region of human rDNA is transcribed in cancer cells [20]. We also have shown that the region ~2 kb upstream of the rRNA promoter is transcriptionally active in normal human cell lines, as well as in glioma and glioblastoma cell cultures [21]. The sequences are given in the Table A1.…”
Section: Introductionmentioning
confidence: 97%
“…It is demonstrated that the pre-promoter region of human rDNA is transcribed in cancer cells [20]. We also have shown that the region ~2 kb upstream of the rRNA promoter is transcriptionally active in normal human cell lines, as well as in glioma and glioblastoma cell cultures [21]. The sequences are given in the Table A1.…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies suggest that IGS has a complex functional organization. RNA-seq analysis of human and murine rDNA has revealed a specific pattern of low-abundance expression over the entire spacer region [15][16][17][18][19][20][21]. One prominent transcription unit includes a 2 kb long segment at the 3 end of IGS, and probably stretches into 5 ETS area [15,20,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq analysis of human and murine rDNA has revealed a specific pattern of low-abundance expression over the entire spacer region [15][16][17][18][19][20][21]. One prominent transcription unit includes a 2 kb long segment at the 3 end of IGS, and probably stretches into 5 ETS area [15,20,[22][23][24]. This region is transcribed by pol I and is involved in rDNA silencing [10,22,[25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar enrichment of RNA pol I factors has been found in human cells approximately 800 bp upstream of transcription start site, with an enrichment of CTCF [ 37 , 48 ]. In the human IGS, a third promoter two kb upstream of the transcription start site in human cells was identified, from which an antisense RNA of unknown function is produced [ 50 ]. The open structure organised with UBF is particularly abundant in ES cells (embryonic stem cells) and mouse embryonic fibroblasts (MEFs), where few histone marks are found in the 47S rRNA gene repeat (35, 37), whereas that of differentiated cells may contain more histones (49).…”
Section: Introductionmentioning
confidence: 99%